AB0802 CYTOKINE PROFILE IN SYNOVIAL FLUID FROM PATIENTS WITH OSTEOARTHRITIS WITH OR WITHOUT CALCIUM CRYSTALS. (June 2019) - Oliviero, Francesca; Galozzi, Paola; Favero, Marta; Tietto, Davide; Lorenzin, Mariagrazia; Ortolan, Augusta; Punzi, Leonardo; Scanu, Anna; Ramonda, Roberta
Abstract : Background: The most important pathogenetic calcium crystals that can be found in synovial fluid (SF) are calcium pyrophosphate (CPP) and basic calcium phosphate (BCP) crystals. We and others have demonstrated that a good portion of patients with osteoarthritis (OA) have these type of crystals in their SF and that they are associated with a higher inflammatory state independently from the disease severity [1]. Objectives: The aim of this study was to investigate the levels of IL-1b, IL-8, IL-6, IL-10, CCL2 and OSMr in the SF of patients affected with OA considering the presence of CPP crystals and the positivity to the alizarin red test (a non-specific test for BCP crystals). A sub-analysis has been conducted subdividing patients according to their Kellgren-Lawrence (K-L) radiographic score. Methods: Synovial fluid was collected from 69 OA consecutive patients diagnosed according to the EULAR criteria. Forty patients were negative to (CPP-) and 29 positive to (CPP+) CPP crystals. A standard analysis was performed for each sample including, white blood cell (WBC) count, differential cell count, crystal search under polarized light microscopy and alizarin red test. The cytokines were measured after appropriate dilutions by ELISA (Thermofisher) and expressed as pg/ml. The Mann-Whitney test was used to investigate differences between the groups of patients positive and negative to CPP; the Spearman rank test was used for correlations, while the Kruskal-Wallis to compare the groups according to the K-L score. Results: With respect to the group of CPP-, the group of CPP+ patients had higher levels of WBC count (251.7±199.3 vs 176.3±161.8 cells/mm3; p=0.004), PMN% (5±7.1 vs 0.44±1.54; p<0.0001), IL-1b (8.92±6.29 vs 4.63±12.2; p<0.0001) and IL-8 (53.73±45.83 vs 26.20±35.94; p=0.0003). No differences were instead observed for the other cytokines considered. We did not find any differences subdividing patients according to the SF positivity to the alizarin red staining. Some correlations were observed in the whole group of patients between IL-1 and IL-8 (p=0.004), IL-1 and PMN (p=0.0006), IL-8 and WBC (p=0.001), IL-8 and PMN (p<0.0001), IL-10 and IL-8 (p=0.04), IL-10 and WBC (p=0.014), CCL2 and IL-6 (0.006). Although no differences have been found analysing the variables in the groups subdivided by the K-L scores, all the cytokines showed higher levels in patients with a K-L score equal to 2. Conclusion: Although associated with higher inflammatory SF indices and IL-1 and IL-8 levels, calcium crystals still play an undefined role in OA. More studies are warranted to evaluate if patients with calcium crystals in their SF might need a more specific treatment. Reference: [1] Frallonardo P, Ramonda R, Peruzzo L, Scanu A, Galozzi P, Tauro L, et al. Basic calcium phosphate and pyrophosphate crystals in early and late osteoarthritis: relationship with clinical indices and inflammation. Clin Rheumatol. 2018Jun7. Disclosure of Interests: Francesca Oliviero: None declared, Paola Galozzi: None declared, Marta Favero: None declared, Davide Tietto: None declared, Mariagrazia Lorenzin: None declared, Augusta Ortolan: None declared, Leonardo Punzi Consultant for: BMS, Fidia, Grunenthal, Menarini, Speakers bureau: BMS, Fidia, Grunenthal, Menarini, Anna Scanu: None declared, Roberta Ramonda: None declared